Establishing Reproducibility and Correlation of Cochlear Microphonic Amplitude to Implant Electrode Position Using Intraoperative Electrocochleography and Postoperative Cone Beam Computed Tomography. Issue 5 (September 2021) - Soulby, Andrew; Connor, Steve; Jiang, Dan; Nunn, Terry; Boyle, Patrick; Pai, Irumee
Abstract : Objectives: The primary objective of this study was to establish the reproducibility of cochlear microphonic (CM) recordings obtained from a cochlear implant (CI) electrode contact during and immediately after insertion. This was achieved by evaluating the insertion angle and calculating the position of the apical electrode contact during insertion, using postoperative cone beam computed tomography (CBCT). The secondary objective was to create individualized patient maps of electrode contacts located within acoustically sensitive regions by correlating the CM amplitude to the electrode position determined using CBCT. Methods: CMs were recorded from a CI electrode contact during and immediately after insertion in 12 patients ( n = 14 ears). Intraoperative recordings were made for a 0.5 kHz tone burst stimulus and were recorded from the apical electrode contact. Postinsertion recordings were made from the odd-numbered electrode contacts (1–15) along the array, using a range of stimulus frequencies (from 0.125 to 2 kHz). The time point at which each electrode contact passed through the round window was noted throughout the insertion, and the CM amplitude at this point was correlated to postoperative CBCT. This correlation was then used to estimate the CM amplitude at particular points within the cochlea, which was in turn compared with the amplitudes recorded from each electrode postoperatively to assess the reproducibility of the recordings. Results: Significant correlation was shown between intraoperative insertion and postinsertion angles at two amplitude events (maximum amplitude: 29° mean absolute error, r = 0.77, p = 0.006; 10% of maximum amplitude: 52° mean absolute error, r = 0.85, p = 0.002). Conclusion: We have developed a novel method to demonstrate the reproducibility of the CM responses recorded from a CI electrode during insertion. By correlating the CM amplitude with the postoperative CBCT, we have also been able to create individualized maps of CM responses, categorizing the cochlea into acoustically responsive and unresponsive regions. If the electrode contacts within the acoustically sensitive regions are shown to be associated with improved loudness discrimination, it could have implications for optimal electrode mapping and placement. Abstract : Supplemental Digital Content is available in the text.